HOUT-16. THE COST EFFECTIVENESS OF TUMOR TREATING FIELDS TREATMENT FOR PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA BASED ON THE EF-14 TRIAL. (5th November 2018) - Guzauskas, Gregory; Wang, Bruce CM; Pollom, Erqi; Stieber, Volker W; Garrison, Lou
Abstract: BACKGROUND: With the EF-14 Trial reporting a 5-year survival rate of 13% for newly diagnosed Glioblastoma (GBM) patients treated with TTFields and maintenance temozolomide (TMZ) chemotherapy, a relevant number of patients will become long-term survivors. The impact on resource utilization from a health-economic standpoint is important for all health care decision-makers and therefore cost-effectiveness of TTFields treatment in first line GBM is assessed from a U.S. health system perspective. METHODS: The incremental cost-effectiveness ratio (ICER) for treatment of newly diagnosed GBM with TTFields and TMZ versus TMZ monotherapy was estimated. We used a 3-state area under the curve model including alive without progression, progressed disease, and death to simulate patient outcomes and a lifetime horizon for survival by integrating the 5-year Kaplan-Meier curves of the EF-14 trial with long-term GBM epidemiology data and U.S. background mortality rates. For the calculation of quality-adjusted life years (QALYs) health utility values reported by Garside et al. were used. Frequency of adverse events (AE) were based on the EF-14 trial. AE and supportive care cost estimates were derived from published literature. We applied a discount of 3% to future survival benefits and costs. Parametrical uncertainty was addressed by one-way and probabilistic sensitivity analyses. RESULTS: We calculated an undiscounted increase in mean survival of 1.8 life years for TTFields plus TMZ versus TMZ alone. After applying the 3% discount rate, the incremental total cost was 188, 637. The incremental cost-effectiveness ratio (ICER) was 150, 452 per life year gained and 197, 336 per QALY gained. CONCLUSIONS: Mean lifetime survival and quality-adjusted survival substantially increases by treatment with TTFields plus TMZ compared to treatment with TMZ alone in newly diagnosed GBM patients. Treatment with TTFields for can be considered cost-effective within the reported range of willingness-to-pay thresholds in the United States based on the results of this analysis.